280 Knowledge brokers: community partners in youth injury prevention research. (1st September 2016) - Romanow, Nicole; McKinlay, Megan; White, Kyla; Rosengarten, Lisa; Hagel, Brent; Emery, Carolyn
Abstract : Background (issue/problem): Building strong partnerships between researchers and the community in youth sport and recreational injury prevention to promote active living and prevent chronic disease is a timely priority. Engaging community partners throughout the research process, from planning to dissemination, is critical to ensure project success, effective knowledge translation (KT) and impact. Description of the problem: Involvement of community stakeholders in research often includes pre-grant solicitation of support or end-phase KT activities. To facilitate optimal and timely input from key stakeholders at all stages of research, the Alberta Program in Youth Sport and Recreational Injury Prevention developed a Knowledge Broker (KB) model. Results (effects/changes): In alignment with research priorities, KBs were identified in relevant community partner organisations (Ever Active Schools, Hockey Calgary, WinSport). KBs bridge the gap between research, education and KT priorities within the academic institution and the community. KB activities include contributing to research questions, intervention development, subject recruitment, implementation and dissemination of findings. Linking researchers and knowledge users facilitates collaboration, a greater understanding of common and diverse goals, and new partnerships. The ideal outcome of these partnerships includes optimal knowledge exchange to maximise the uptake of research evidence for the greatest public health impact. A financial contribution from the research program helps support the commitment of KBs. Conclusions: The integrated nature of the research program with academic and community stakeholder partnerships, creates an ideal setting for enhancing the impact of KT. KB involvement contributes significantly to achieving research objectives. KB contributions optimise the translation of research findings into injury prevention practice, programs and policies.